The theory of the sentence secondary members in D. M. Ovsianyko-Kulykovskyі’s syntax studies and its practical implementation - Hanna Aniutina (Вісник Харківського національного університету імені В. Н. Каразіна. Серія Філологія. Vìsnik Harkìvsʹkogo nacìonalʹnogo unìversitetu ìmenì V.N. Karazìna. Serìâ Fìlologìâ.)
A valuable contribution to the development of views on sentence syntax problems was made by the outstanding scientist of Kharkiv Linguistic School D. M. Ovsianyko-Kulykovskyі, in particular the views on such problems as the structure of the simple sentence, the ways of expressing each member of the sentence and its syntactical relations. The aim of this article is to analyze the classification of secondary members of the sentence, objects in particular, suggested by D. M. Ovsianyko-Kulykovskyі, the influence of his studies on modern syntax theories and suggest criteria of discovering the presence of object relations between the verb and its direct object.